2003
DOI: 10.1148/radiol.2272020660
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Lesions of the Breast: Sonographic-Pathologic Correlation

Abstract: Symptomatic complicated cysts generally warrant aspiration. All clustered microcysts were benign, but further study is required. Cystic lesions with thick indistinct walls and/or thick septations (> or =0.5 mm), intracystic masses, and predominantly solid masses with eccentric cystic foci should be examined at biopsy; 18 of 79 of such complex cystic lesions proved malignant in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
185
4
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(207 citation statements)
references
References 42 publications
(28 reference statements)
8
185
4
10
Order By: Relevance
“…1B) or liquideliquid levels (e.g. galactocele) [24]. They should be evacuated if they are symptomatic or if there are diagnostic doubts.…”
Section: Cystsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) or liquideliquid levels (e.g. galactocele) [24]. They should be evacuated if they are symptomatic or if there are diagnostic doubts.…”
Section: Cystsmentioning
confidence: 99%
“…Morphological features which are suspicious for malignancy are thick isoechoic intracystic septations, mural nodules, fibrovascular stalk in the solid components and a microcystic appearance or microlobulated contour [3,24,25]. In 85%e90% of cases the lesion is a benign intracystic papilloma, and in the remaining 10%e15% of cases it is a papillary lesion with atypia or intracystic papillary carcinoma.…”
Section: Cystsmentioning
confidence: 99%
“…according to BI-RADS [14] and the sonographic cystic mass classification described by Berg and colleagues [13].…”
Section: Mucocele-like Breast Tumors As Cystic Lesionsmentioning
confidence: 99%
“…It has been suggested that on mammograms, mucocele-like tumors associated with malignancy have microcalcifications more frequently and to a greater extent than do benign mucocele-like tumors [7,11]. Two reports [12,13] have described attempts to differentiate benign and malignant cystic lesions in various pathologic conditions.The purpose of our study was to review the mammographic and sonographic findings of mucocele-like tumors and to correlate the imaging findings with the pathologic findings. A secondary purpose was to evaluate the differential radiologic findings of pure mucocelelike tumors and mucocele-like tumors associated with ADH or malignancy of the breast Because mucocele-like tumors may be associated with these other conditions, it is difficult to differentiate a pure mucocele-like tumor from a malignant tumor with fine-needle aspiration or core needle biopsy findings, and complete excision is recommended [5][6][7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation